2013
DOI: 10.1111/ijac.12138
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on CuCa3Ti4O12 Modified BiFeO3‐Based Perovskite Ceramics

Abstract: (BiFeO3)1−x–(CuCa3Ti4O12)x (x = 0.00, 0.10 and 0.20) ceramics had been prepared via the mixed route. The crystal structure transformation of BiFeO3 (BFO) from rhombohedral to pseudotetragonal phase was induced by 20 mol% CuCa3Ti4O12 (CCTO). Impedance measurements suggested the increase in grain boundary resistance, and CCTO addition could block the conduction path and stabilize the motion of defects. The dielectric constant and the loss tangent of BFO as a function of frequency were found to be incremental on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…[61][62][63][64][65] Based on the steps of the degradation reactions of organic pollutants, similar to the water splitting reaction, the key to improve the photocatalytic activity is to suppress electron-hole recombination and tailor the BG because the BG width is one of the most critical properties of photocatalytic materials and determines the amount of solar energy to be absorbed and that is available for conversion. The development of new photocatalysts with reduced BGs to successfully utilize visible light, which is the main part of solar light, is of great importance.…”
Section: Perovskite Materials As Catalysts For Photocatalytic Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[61][62][63][64][65] Based on the steps of the degradation reactions of organic pollutants, similar to the water splitting reaction, the key to improve the photocatalytic activity is to suppress electron-hole recombination and tailor the BG because the BG width is one of the most critical properties of photocatalytic materials and determines the amount of solar energy to be absorbed and that is available for conversion. The development of new photocatalysts with reduced BGs to successfully utilize visible light, which is the main part of solar light, is of great importance.…”
Section: Perovskite Materials As Catalysts For Photocatalytic Reactionsmentioning
confidence: 99%
“…64,65,100 Among the various doping processes, Sr and Mn were used to dope BiFeO 3 and LaFeO 3 perovskite catalysts at the A site and B site, respectively, which resulted in reduced particle sizes of the perovskite. Many researchers have focused on developing highly active photocatalysts for the degradation of organic dyes using doping foreign elements at the A site or B site to reduce the recombination rate of electron-hole pairs by reducing the particle size.…”
Section: Degradation Of Organic Dyesmentioning
confidence: 99%
“…7(a) and 7(c), indicating a coexistence of antiferromagnetic and weak ferromagnetism. [42] According to the local density approximation, Li et al reported a metastable FM state in CCTO by means of the spin-polarized moment method and the fixed-spin-moment method, indicating an AFM-FM transition. [4] The AFM state is calculated to be 84 meV lower in energy than the FM state by the generalized gradient approximation (GGA).…”
Section: Magnetism Of Cctomentioning
confidence: 99%